Genre-Based Writing Model: A Study on Politeknik Negeri Jakarta’s Applied Master Thesis ‘Results and Discussions’ - Nur Hasyim; Ade Sukma Mulya; Darul Nurhanah (Politeknik Negeri Bali, 2019)
It has been well understood that writing the “result and discussion” part of a Thesis is a challenging task. The task had been found to be highly challenging by the students of Applied Master Program. The current study employed genre theory to investigate the writing model prototype in use for the “results and discussions” parts of Applied Master Thesis. Genre theory was developed by Swales (1990), Martin & Rose (2007), and Wiratno & Santosa (2011). The research paradigm employed for the current study is the developmental research paradigm. The current study is motivated by the limited number of studies on issues regarding the writing of the “results and discussions” part of a Thesis. The current study found (1) the main requirement that needs to be written in “results and discussions” parts is describing the results and discussing the results, based on the theory in use. The “results and discussions” parts need to be written by using descriptive text, report text, and discussion text basis, (2) descriptive text is a kind of text that explains something as it is. The structure of the descriptive text is (a) thing described generally, and (b) parts of things described. (3) Report text is a text that used to classify data. The structure of report text is (a) something reported and (b) class or subclass from something. (iv) Discussion text is a text that explains the phenomenon from two sides: pro and contra. The structure of discussion is (a) issue statement, (b) pro argumentation, (c) contra argumentation, (d) conclusion/recommendation. (4) Descriptive text, report text, and discussion text have linguistic characteristics, such as the verb, adjective, and conjunction that commonly can be used in order writers can make the research results and discussion part correctly and quickly.